Baby Einstein. Season 1 [videorecording (DVD)] - Aigner-Clark, Julie; Aigner-Clark, Julie; Privett, Dave; Privett, June (Dreamscape Media, 2025)
Baby Einstein helps parents cultivate their baby's curiosity through experiences of shared discovery and creativity. Your baby's knowledge will grow as they explore the world with friendly characters, discover numbers and letters, and nurture musical appreciation with classic lullabies and nursery rhymes.